Delayed iron improves iron status without altering malaria risk in severe malarial anemia. Issue 5 (1st February 2020) - Cusick, Sarah E; Opoka, Robert O; Ssemata, Andrew S; Georgieff, Michael K; John, Chandy C
ABSTRACT: Background: WHO guidelines recommend concurrent iron and antimalarial treatment in children with malaria and iron deficiency, but iron may not be well absorbed or utilized during a malaria episode. Objectives: We aimed to determine whether starting iron 28 d after antimalarial treatment in children with severe malaria and iron deficiency would improve iron status and lower malaria risk. Methods: We conducted a randomized clinical trial on the effect of immediate compared with delayed iron treatment in Ugandan children 18 mo–5 y of age with 2 forms of severe malaria: cerebral malaria (CM; n  = 79) or severe malarial anemia (SMA; n  = 77). Asymptomatic community children (CC; n  = 83) were enrolled as a comparison group. Children with iron deficiency, defined as zinc protoporphyrin (ZPP) ≥ 80 µmol/mol heme, were randomly assigned to receive a 3-mo course of daily oral ferrous sulfate (2 mg · kg –1 · d –1 ) either concurrently with antimalarial treatment (immediate arm) or 28 d after receiving antimalarial treatment (delayed arm). Children were followed for 12 mo. Results: All children with CM or SMA, and 35 (42.2%) CC, were iron-deficient and were randomly assigned to immediate or delayed iron treatment. Immediate compared with delayed iron had no effect in any of the 3 study groups on the primary study outcomes (hemoglobin concentration and prevalence of ZPP ≥ 80 µmol/mol heme at 6 mo, malaria incidence over 12 mo). However, after 12 mo, children with SMA in the delayed compared with the immediate arm had a lower prevalence of iron deficiency defined by ZPP (29.4% compared with 65.6%, P  = 0.006), a lower mean concentration of soluble transferrin receptor (6.1 compared with 7.8 mg/L, P  = 0.03), and showed a trend toward fewer episodes of severe malaria (incidence rate ratio: 0.39; 95% CI: 0.14, 1.12). Conclusions: In children with SMA, delayed iron treatment did not increase hemoglobin concentration, but did improve long-term iron status over 12 mo without affecting malaria incidence. This trial was registered at clinicaltrials.gov as NCT01093989.